Talent management in practice : an integrated and dynamic approach - Thunnissen, Marian (Emerald Publishing Limited, 2017)
Talent Management (TM) is an issue of critical importance for today's senior managers. Employers acknowledge that an engaged, skilled and motivated workforce is key to achieving growth and competitive advantage. Organizations are hiring TM officers and implementing TM strategies and programs to attract and retain the best employees. Yet many organizations still find it difficult to develop a coherent and successful TM approach. Academic research does not give much support in finding the right solutions: despite the enormous expansion of research on the topic, ambiguity about definitions and conceptual boundaries remains. Moreover, there is little knowledge about the nature of TM in practice and how it evolves over time. Talent Management in Practice offers an integrated and contextualized framework that addresses both the nature of TM in organizations and its ever-changing dynamics. The approach is based, on the one hand, upon lessons learned from previous empirical research on TM, and on the other hand, upon established theoretical frameworks from related academic fields. The result is a unique bridge between theory and TM in practice. This volume develops a model that can guide TM researchers in their future research, and since it is presented in an accessible and jargon-free format, it provides a touchstone for managers and practitioners as they implement and improve their TM approaches.- Resumé vydavatel